Features of Lactation Period of Cows of Different Breeds and Co-Breeds - F.R. Sattorov, U.Т. Rakhimov (American Journal of Biodiversity, 2025)
The lactation period is a critical physiological phase that directly affects the overall productivity and reproductive efficiency of dairy cattle. This study focuses on the distinctive characteristics of the lactation period among cows of various pure breeds and crossbreeds. Through comparative analysis, the research evaluates key indicators such as the duration of lactation, peak milk yield, persistency, and milk composition across different genetic groups. The study includes Holstein, Simmental, and crossbred cows maintained under uniform feeding and housing conditions. Results indicate that breed significantly influences lactation traits, with Holstein cows demonstrating higher peak yields and Simmental cows showing more stable lactation curves. Crossbreeds displayed a balanced profile, often combining the advantageous traits of both parental breeds. These findings emphasize the importance of breed selection and crossbreeding strategies in optimizing lactation performance and improving overall herd efficiency in dairy farms